The technology transfer in the development of the small and medium metal-mechanic ecuadorian enterprise - Quezada Torres, Walter David (2018)
Fil: Quezada Torres, Walter David. Universidad Central Marta Abreu de Las Villas. Facultad de Ingeniería Mecánica e Industrial; Cuba.